The Catalytic Intermediate Stabilized by a “Down” Active Site Loop for Diaminopimelate Decarboxylase from Helicobacter pylori: ENZYMATIC CHARACTERIZATION WITH CRYSTAL STRUCTURE ANALYSIS - Hu, Tiancen (American Society for Biochemistry and Molecular Biology, 2008)
The meso-diaminopimelate decarboxylase (DAPDC, EC 4.1.1.20) catalyzes the final step of l-lysine biosynthesis in bacteria and is regarded as a target for the discovery of antibiotics. Here we report the 2.3Å crystal structure of DAPDC from Helicobacter pylori (HpDAPDC). The structure, in which the product l-lysine forms a Schiff base with the cofactor pyridoxal 5′-phosphate, provides structural insight into the substrate specificity and catalytic mechanism of the enzyme, and implies that the carboxyl to be cleaved locates at the si face of the cofactor. To our knowledge, this might be the first reported external aldimine of DAPDC. Moreover, the active site loop of HpDAPDC is in a “down” conformation and shields the ligand from solvent. Mutations of Ile(148) from the loop greatly impaired the catalytic efficiency. Combining the structural analysis of the I148L mutant, we hypothesize that HpDAPDC adopts an induced-fit catalytic mechanism in which this loop cycles through “down” and “up” conformations to stabilize intermediates and release product, respectively. Our work is expected to provide clues for designing specific inhibitors of DAPDC.